PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP PERINGKAT SUKUK DENGAN INFLASI DAN SUKU BUNGA SEBAGAI VARIABEL MODERASI - Gustiani, Santi; Eriswanto, Elan; Martaseli, Evi (Jurnal Akuntansi AKTIVA, 2025)
One of the securities traded is sukuk or Islamic bonds. Investors interested in purchasing bonds must consider several factors, such as the sukuk rating. This study aims to examine the influence of profitability and liquidity on sukuk ratings, as well as the moderating role of inflation and interest rates in this relationship. Profitability and liquidity are fundamental factors often used to assess a company's financial performance, which in turn affects the rating of financial instruments such as sukuk. This study employs a quantitative approach, with data collection using documentation techniques. The sample in this study consists of sukuk-issuing companies listed on the Indonesia Stock Exchange whose sukuk ratings are known by Pefindo during the 2019-2023 research period. The sampling technique was conducted using purposive sampling, with specified criteria resulting in 10 sample companies. Data analysis was conducted using Spreadsheet and SPSS 29.0.2.0 software. The results of this study indicate that profitability does not affect sukuk ratings. Liquidity has a negative effect on sukuk ratings. This study also examines the moderating variables of inflation and interest rates, which show that inflation and interest rates do not strengthen or weaken the effect of profitability on sukuk ratings or the effect of liquidity on sukuk ratings.